Towards determining Nigeria's economic growth path: A balance-of-payments constrained growth approach - Yohanna Panshank; Ifran Civcir; Ozdeser (EconomiA, 2020)
This paper examines Nigeria's long run growth path using the externally and internally constrained version of Thirlwall's growth model from 1982 to 2015. The present study modifies the SCA-BOPCG to take into account the effects the foreign contents in exports growth and the domestic investment. Three Stage Least Squares method is used to obtain the required elasticities for the estimation of the domestic income growth. The study affirms the robustness and validity of the modified model in determining the growth path for Nigeria. The outcome of the empirical study reveals that Nigeria's economic growth process is balance-of-payment constrained. Even though monetary policies improve growth performance, Nigeria sustainably grows faster with policies aiming at improving external balance or reducing the import components of demands, increasing export share to products with high elasticity of demand as well as keeping budget deficits within the universally acceptable limits.
Keywords: F43; E12; O24; 330; Internal and external imbalances; Relative prices and income elasticities; Balance-of-payment equilibrium growth rates; Export and investment requirement of import